Contemporary state and problems of the emergency neurosurgery care at acute brain vascular damage - Yu. P. Zozulia (Ukrainian Neurosurgical Journal, 2005)
Speech at the conference "Topical issues of emergency neurosurgery" (Ternopil, September 21-23, 2005)